Efficiency of Dogs in Locating Bobwhites - Forest E. Kellogg; Gary L. Doster (National Quail Symposium Proceedings, 2017)
The efficiency of dogs in locating bobwhites (Colinus virginianus) was studied on Tall Timbers Research Station, Leon County, Florida. Numbers of bobwhites present on two study areas were determined in six different years with the Lincoln Index method. Numbers of bobwhites found on bird dog censuses and numbers of bobwhites flushed while methodically hunting the study areas were recorded for comparison with Lincoln Index data. Numbers of bobwhites found with both methods involving bird dogs were substantially less than those numbers determined with the Lincoln Index census technique.